A new apparatus for the concurrent measurement of friction and permeability evolution in fault gouge. (September 2019) - Li, Ziyan; Elsworth, Derek; Wang, Chaoyi; Im, Kyungjae
Abstract: We introduce a new miniature double direct shear (mini-DDS) apparatus, housed within a standard-triaxial (TEMCO) pressure vessel, capable of concurrently measuring the evolution of frictional strength, stability, healing and along-fault permeability under in situ conditions of stress and temperature. The apparatus accommodates gouge samples (25 mm × 32 mm) and intact rock samples with confining and shear stresses and pore pressures up to ∼26 MPa. Permeability may be measured with applied flow rates ranging from 1.67 × 10 −11 to 3.6 × 10 −6 m 3 /s to a flow accuracy of 0.5% representing a lower bound of permeability >2.2 × 10 −18 m 2 . Sliding velocities are in the range 0.1 μm/s to 0.67 cm/s with a frame stiffness of 0.067 kN/μm. We describe protocols and procedures for calibration and experiments and note the potential of the apparatus for both rapid and extended-duration measurements of friction-permeability evolution and healing. The apparatus returns measurements of friction and stability of reference materials of F110 quartz consistent with the literature while additionally allowing the concurrent measurement of permeability. Permeability of F110 quartz evolves in slide-hold-slide (SHS) experiments with increases during holds and decreases during subsequent slides. These observations are consistent with grain crushing and resultant wear products that reduce that permeability by clogging during slides with unclogging of the major fluid channels occurring during shearing.